Compliance Behaviour Amidst Ambiguous Information: An Exploratory Study in the Context of COVID-19. (November 2022) - Aggarwal, Divya; Rajasulochana, Subramania Raju; Elembilassery, Varun
COVID-19 pandemic is an ambiguous situation due to the uncertainty associated with the outcome of the situation. This article aims at exploring the knowledge behaviour gap during a pandemic like COVID-19. The findings of this study indicate that individuals perceive different forms of ambiguity in different ways. Findings also suggest that, during a pandemic, attitude towards ambiguity and confidence in self-health significantly impact compliance behaviour. Interestingly, the findings also indicate that knowledge and perception about the context are not significantly associated with compliance behaviour. This study is one of the earliest attempts to understand the knowledge behaviour gap during a pandemic and contributes to the research literature by attempting a cross-fertilization of concepts from different streams of literature. This study also discusses the practical implications for the health sector, in particular health communication. JEL Codes: C9, D10, D81, D90